MIRERC 040/2025: A Two-Stream Deep Learning Approach for Freshness Classification in Beef - Muthomi, Martin; Dr. Samson Munialo; Dr. Mary Mwadulo (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Meat is an essential part of the human diet, providing necessary nutrients and protein(Cocking et al., 2020). However, during storage the quality of beef can go down due to chemical spoilage thereby posing danger to human health (Catherine et al., 2021). The freshness of meat plays a crucial role in determining its taste, nutritional value and potential health risks hence quality (freshness) and safety are of paramount importance(Osei Mensah et al., 2022). One way to assess the freshness of meat is through inspection. Meat’s shelf life will vary depending on how it was processed or how it is stored. There is need for strict inspection measures since consumption of spoiled or adulterated beef has serious implications on consumers’ health. In Kenya, as meat consumption is high, beef inspection becomes very essential for food safety and quality. In Kenya, annual red meat production is estimated at 362,815 Metric Tonnes (MT) of which beef constitutes about 286,000 MT(Aklilu et al., 2002). Although there are around 2500 export slaughterhouses available, only about 500 meat inspectors have been certified thus leaving a massive inspection capacity gap (KEPSA 2019) posing a challenge to meat inspection. Kenyan law as provided for in Kenya Meat Control Act (Cap 356) prescribes that meat inspection should be performed exclusively by veterinarians. The process of Meat Inspection is clearly outlined in the Kenya Meat Control Act (Cap 356) (1972). A thorough journey, which begins a day before the animal is killed and ends at the market where meat ends up, involves inspections at the export slaughter house, ante mortem checks, detailed post mortems and life at the shelves. All these processes are supposed to be done by qualified meat inspectors who unfortunately are in short supply. It is this shortage of personnel that results into a situation where inspecting officers find themselves overstretched and as a result, they tend to focus on inspections at the slaughter houses and cannot effectively concentrate on ensuring freshness of meat stocked on shelves. This condition strains already existing workers and calls into question the efficiency of meat inspection protocols as well as consumer confidence in beef safety and quality.